Survei Cemaran Mikroba dan Mutu Ikan Tongkol (Euthynnus Affinis) Segar - Dewi Sartika; Anitsa Asrining Puri; Subeki User (Inovasi Pembangunan : Jurnal Kelitbangan, 2016)
According to Lu et al. (2010), one of the fishing products that has high in nutritionis is swordfish. Swordfish poisoning that often occurs is histamine poisoning (scombroid fish poisoning). This is caused by pathogen bacterial contamination such as Escherichia coli, Salmonella, Vibrio cholerae, Enterobacteriacea, etc (Kurniawan et al, 2012). The aim ofthis researchwas to know the difference of microbes contamination and physical appearance on the swordfish (Euthynnus affinis) from traditional markets, modern and fish auction markets in Bandar Lampung.This research was done in two stages. The first stage was done collecting swordfish samples randomlyfrom traditional, modern, and auction markets in Bandar Lampung. There were 13 traditional markets, 7 modern markets, and 2 warehouse markets in Bandar Lampung. The second stage of research were do total analysis of microbes, the total plate count (TPC) test, Eschericia colitest, Salmonella sp.test, and freshness level on swordfish using organoleptic test. Then the data of observed total colony and the results data of the organoleptic test were analyzed using BNJ test. The conclusion of this research were be found a difference and swordfishfreshness level on traditional, modern, and auction markets in Bandar Lampung.The lowest value of total plate count 6,5 x 104, Eschericia coli1,53 x 104, and Salmonella sp3 x 101.